Penggunaan Augmented Reality (AR) dalam Pembelajaran Pendidikan Agama Islam di SMA Negeri 2 Ungaran - Liestya, Serani Dara; Isnaini, Isnaini; Adibah, Ida Zahara (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
This study aims to examine the use of Augmented Reality (AR) technology in Islamic Religious Education (IRE) learning at the senior high school level, in response to students' low interest due to conventional and less interactive teaching methods. A qualitative research method was employed through observations and interviews with students, IRE teachers, and the vice principal for curriculum. The results indicate that AR enhances students’ understanding, interest, and participation through engaging interactive visualizations and active teacher-student interaction. Supporting factors include Wi-Fi access and students’ enthusiasm for technology-based learning, while challenges involve the need for adequate devices, stable internet connectivity, and teachers’ proficiency in using AR. In conclusion, AR is an effective innovation for improving the quality and interactivity of IRE learning experiences.ABSTRAKPenelitian ini bertujuan mengkaji penggunaan Teknologi Augmented Reality (AR) dalam pembelajaran Pendidikan Agama Islam (PAI) di tingkat SMA, mengingat rendahnya minat siswa akibat metode yang kurang interaktif. Metode penelitian yang digunakan adalah kualitatif melalui observasi dan wawancara dengan siswa, guru PAI, dan Waka Kurikulum. Hasil menunjukkan bahwa AR mampu meningkatkan pemahaman, minat, dan partisipasi siswa melalui visualisasi interaktif yang menarik serta interaksi aktif antara guru dan siswa. Faktor pendukungnya meliputi akses Wi-Fi dan ketertarikan siswa terhadap teknologi, sedangkan kendalanya adalah kebutuhan perangkat, koneksi internet, dan penguasaan teknologi oleh guru. Kesimpulannya, AR merupakan inovasi efektif dalam meningkatkan kualitas dan pengalaman belajar PAI secara lebih interaktif.